TWO NEW SPECIES OF FREYCINETIA (PANDANACEAE) FROM SUMATRA, INDONESIA - PASARIBU, NURSAHARA (REINWARDTIA, 2010)
PASARIBU, N. 2010. Two new species of Freycinetia (Pandanaceae) from Sumatra. Reinwardtia 13(2): 147-150. -A study of Freycinetia Gaud. (Pandanaceae) conducted in Sumatra has revealed a number of new species. Two are described and illustrated here.